Weekly rainfall variability and probability analysis for Coimbatore in respect of crop planning (MAUSAM, 2014)
Daily rainfall data of 30 years (1981-2010) of Coimbatore were used for weekly analysis to study the variability and the probability level of occurrence. The study indicated that rainfall amount of more than 25 mm under 50 per cent probability was observed in the standard weeks from 40th to 45th with 41st week being 14.6 mm. The chance of getting 25 mm weekly rainfall with 50 per cent probability was noticed from 39th to 46th standard week covering eight weeks. The CV of weekly rainfall analysis indicated dependable rainfall from 37th to 48th standard weeks irrespective of quantity of rainfall to be received. Drought resistant short duration pulses and sorghum can be grown within the growing period from 39th to 46th standard weeks